Tissue Oxygenation in Response to Different Relative Levels of Blood-Flow Restricted Exercise - Reis, Joana F.; Fatela, Pedro; Mendonca, Goncalo V.; Vaz, Joao R.; Valamatos, Maria J.; Infante, Jorge; Mil-Homens, Pedro; Alves, Francisco B. (Frontiers in Physiology, 2019)
Blood flow restrictive (BFR) exercise elicits a localized hypoxic environment compatible with greater metabolic stress. We intended to compare the acute changes in muscle microvascular oxygenation following low-intensity knee extension exercise, combined with different levels of BFR. Thirteen active young men (age: 23.8 ± 5.4 years) were tested for unilateral knee extension exercise (30+15+15+15 reps at 20% one repetition maximum) on 4 different conditions: no-BFR (NOBFR), 40, 60 and 80% of arterial occlusion pressure (AOP). Deoxyhaemoglobin+myoglobin concentration Deoxy[Hb+Mb], total haemoglobin [T(H+Mb)] and tissue oxygen saturation [TOI] were measured on the vastus lateralis muscle using near-infrared spectroscopy (NIMO, Nirox srl, Brescia, Italy). The magnitude of change in Deoxy[Hb+Mb]during exercise was similar between 60 and 80% AOP. Overall, compared to that seen during 60 and 80% AOP, NOBFR as well as 40%AOP resulted in a lower magnitude of change in Deoxy[Hb+Mb] (p < 0.05). While the oxygen extraction decreased during each inter-set resting interval in NOBFR and 40%AOP, this was not the case for 60 or 80%AOP. Additionally, TOI values obtained during recovery from each set of exercise were similarly affected by all conditions. Finally, our data also show that, when performed at higher restrictive values (60 and 80%), BFR exercise increases total Deoxy[Hb+Mb]extraction (p < 0.05). Taken together, we provide evidence that BFR is effective for increasing deoxygenation and reducing tissue oxygenation during low-intensity exercise. We also showed that when using low loads, a relative pressure above 40% of the arterial occlusion pressure at rest is required to elicit changes in microvascular oxygenation compared with the same exercise with unrestricted conditions.